TOKSISITAS EKSTRAK KARANG LUNAK Cespitularia sp. DARI TELUK MANADO PROVINSI SULAWESI UTARA - Marsitasari Tandiongan; Robert A Bara (JURNAL PESISIR DAN LAUT TROPIS, 2021)
Secondary metabolites produced by marine organisms commonly have unique chemical structures and very interesting pharmacological activities. Marine organisms that have the most chemical conent are produced by marine invertebrates, followed by marine plants. Groups that include marine invertebrates include: sponges, bryozoans, cnidarians and tunicates. Soft coral, which is one of the marine invertebrates, has biological activities, such as antifungal, cytotoxic, antineoplastic, antimicrobial, HIV inhibitor and anti-inflammatory. This study aims to determine the Â value of the soft coral extract Cespitularia sp. taken from Manado Bay by the Brine Shrimp Lethality Assay (BSLA) method. This toxicity test was carried out quantitatively by analyzing data based on the number of deaths caused by the test extract of Artemia sp. The results obtained based on data analysis namely the value of the soft coral extract Cespitularia sp. is 53.27 ppm, this means that the extract can be developed as an anticancer drug candidate due to below below to 1000 ppm. Soft coral Cespitularia sp. categorized as toxic based on the Meyer classification or moderately toxic based on the Tanamatayarat classification and very toxic based on the Clarkson classification.Keywords: Soft coral; Cespitularia sp.; Toxicity;